The effectiveness of the application of Articulate Storyline 3 learning object on student cognitive on Basic Computer System courses - I Gede Partha Sindu; Gede Saindra Santyadiputra; Agus Aan Jiwa Permana (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2020)
This study aimed to determine the effectiveness of applying learning objects based on Articulate Storyline 3 on student cognitive competence in the Basic Computer System course in the Informatics Engineering Education Study Program at the Ganesha University of Education. This type of research was descriptive quantitative with a pre-experimental research design involving one experimental class. The populations used in this study were all semester 1 students of the Informatics Engineering Education study program in the Basic Computer Systems course in the odd semester of the 2020-2021 academic year. Random sampling was using a simple random sampling technique. The average pretest result was 57.12, and the posttest average is 79.81. The paired pretest-posttest t-test resulted in the Sig. equal to 0.000, which indicates that there is a significant difference in the average pretest and posttest results. The percentage of student responses to the learning model is 64.19. This shows that self-confidence in learning objects based on Articulate Storyline 3 on student cognitive abilities